PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF DENGAN STRATEGI BOWLING KAMPUS TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI I RAMBAH SAMO - Nila, Ikar; Afri, Lusi Eka; Deswita, Hera (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2015)
The research to see the effect of the Cooperative learning model with Bowling Campus Strategy of product learning math class VIII SMP Negeri 1 Rambah Samo. This type of research a quasi-experimental research with the study design Randomized Subjects Posttes Only Control Group Design. Then tested for normality and homogeneity tests then proceed to test the hypothesis with the t test by significant level was 0.05. so that, t value was 3,799 while ttable was 2,002. This concluded that tvalue > ttable so reject H0. It concluded that there were the effect of the Cooperative learning model with Bowling Campus Strategy of product learning math class VIII SMP Negeri 1 Rambah Samo.